Peran Aksara Arab Melayu dalam Pelestarian - Munawarah, Raudhatul; Mawaddah, Sri (Abdurrauf Science and Society, 2025)
The Arabic-Malay script is a writing system derived from modified Arabic script, adapted to transcribe the Malay language. Its existence has made a significant contribution to the preservation of the language and culture of the Malay people. This article examines the crucial role of the Arabic-Malay script, including its function as a medium for transmitting knowledge and Islamic teachings, a symbol of cultural identity, a tool for preserving the written form of the Malay language, and a means of character education rooted in local values. Despite its historical and cultural importance, this script now faces serious challenges due to the dominant influence of the Latin script in the modern era. Therefore, strategic and sustainable efforts are needed to revive the use of the Arabic-Malay script through education, manuscript digitization, and strengthening cultural literacy. This article emphasizes the urgency of preserving the Arabic-Malay script as a priceless heritage of Malay civilization. Abstrak :  Aksara Arab Melayu adalah bentuk sistem tulisan yang berasal dari huruf Arab yang telah disesuaikan untuk menuliskan bahasa Melayu. Keberadaannya memiliki kontribusi yang besar dalam menjaga kelestarian bahasa dan budaya masyarakat Melayu. Tulisan ini mengulas beragam peran penting aksara Arab Melayu, mulai dari alat penyebaran ilmu pengetahuan dan ajaran Islam, penanda identitas budaya, sarana pelestarian bahasa Melayu dalam bentuk tulisan, hingga media pendidikan karakter yang tertanam pada nilai-nilai lokal. Meskipun memiliki nilai sejarah dan budaya yang tinggi, aksara ini kini menghadapi tantangan serius karena pengaruh dominan aksara Latin di era modern. Oleh karena itu, diperlukan langkah-langkah strategis dan berkesinambungan untuk menghidupkan kembali penggunaan aksara Arab Melayu melalui jalur pendidikan, digitalisasi naskah, serta penguatan literasi budaya. Artikel ini menekankan urgensi menjaga dan melestarikan aksara Arab Melayu sebagai salah satu warisan peradaban yang tak ternilai. Kata kunci:  Aksara Arab Melayu, pelestarian budaya, identitas Melayu, bahasa Melayu klasik, warisan keilmuan.